ChemInform Abstract: One‐Pot Synthesis of Aryloxypropanediols from Glycerol: Towards Valuable Chemicals from Renewable Sources. Issue 26 (6th June 2013) - Truscello, Ada M.; Gambarotti, Cristian; Lauria, Mirvana; Auricchio, Sergio; Leonardi, Gabriella; Shisodia, Suresh U.; Citterio, Attilio
Abstract The title compounds are obtained by a regioselective reaction of phenols and glycerol using diethyl carbonate as promoter.